Bank Concentration and Bank Stability during the COVID-19 Pandemic - Sukisno Selamet Riadi; Michael Hadjaat; Rizky Yudaruddin (Emerging Science Journal, 2022)
Objectives: The banking sector has been impacted more negatively by the COVID-19 pandemic. At the same time, bank concentration and capitalization stabilize banking systems during times of crisis. This study evaluated the monthly financial reports of all commercial banks in Indonesia to investigate the joint impact of the COVID-19 pandemic and bank concentration on bank stability. Moreover, this study was conducted to determine whether adequate capitalization could enhance the positive effect of the interaction between COVID-19 and bank concentration during the pandemic. Methods/Analysis: Using 108 commercial banks between March 2020 and May 2021, data were analyzed using the fixed-effects estimator with heteroskedasticity and within-panel serial correlations for robust standard errors. Several robustness checks were performed to ensure that the results were accurate and consistent. Findings: Subsequently, the impact of the pandemic and bank concentration was determined to be significant and adverse, though their interplay was strong enough to promote bank stability. This highlights the importance of adequate capitalization in enhancing the beneficial effects of the interaction between COVID-19 and bank concentration on bank stability. Novelty /Improvement: Hence, these ﬁndings contribute to the literature on bank stability and have important policy implications for the banking sector during this pandemic.JEL Classifications: E51, G20, G21. Doi: 10.28991/esj-2022-SPER-018 Full Text: PDF